New fecal bacterial signature for colorectal cancer screening reduces the fecal immunochemical test false-positive rate in a screening population. - Marta Malagón; Sara Ramió-Pujol; Marta Serrano; Joan Amoedo; Lia Oliver; Anna Bahí; Josep Oriol Miquel-Cusachs; Manel Ramirez; Xavier Queralt-Moles; Pau Gilabert; Joan Saló; Jordi Guardiola; et al. (PLoS ONE, 2020)
Guidelines recommend routine screening for colorectal cancer (CRC) in asymptomatic adults starting at age 50. The most extensively used noninvasive test for CRC screening is the fecal immunochemical test (FIT), which has an overall sensitivity for CRC of approximately 61.0%-91.0%, which drops to 27.0%-67.0% for advanced adenomas. These figures contain a high false-positive rate and a low positive predictive value. This work aimed to develop a new, noninvasive CRC screening tool based on fecal bacterial markers capable of decreasing FIT false-positive rates in a FIT-positive population. We defined a fecal bacterial signature (RAID-CRC Screen) in a proof-of-concept with 172 FIT-positive individuals and validated the obtained results on an external cohort of 327 FIT-positive subjects. All study participants had joined the national CRC screening program. In the clinical validation of RAID-CRC Screen, a sensitivity of 83.9% and a specificity of 16.3% were obtained for the detection of advanced neoplasm lesions (advanced adenomas and/or CRC). FIT 20 μg/g produced 184 false-positive results. Using RAID-CRC Screen, this value was reduced to 154, thus reducing the false-positive rate by 16.3%. The RAID-CRC Screen test could be implemented in CRC screening programs to allow a significant reduction in the number of colonoscopies performed unnecessarily for FIT-positive participants of CRC screening programs.